Pengaruh Lingkungan Kerja dan Pengalaman Kerja terhadap Loyalitas Kerja : Sensus pada Karyawan PT. Daya Anugrah Mandiri - Cindy Meilani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine and analyze the effect of work environment and work experience on work loyalty (census on employees of PT. Daya Anugrah Mandiri). The method used in this study is causality through a census approach. With a research sample of 60 employees of PT. Independent Power of Grace. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that the work environment has a very good rating classification, work experience has a very good rating classification, while work loyalty has a good classification for employees of PT. Independent Power of Grace. Together the Work Environment and Work Experience have a significant influence on Work Loyalty on Employees of PT. Independent Power of Grace. Partially, the work environment has no significant effect on employee loyalty at PT. Independent Power of Grace. Partially, work experience has a significant effect on work loyalty to employees of PT. Independent Grace